Variasi Pola Trauma pada Kasus Kematian Akibat Tindak Kekerasan Berdasarkan Data Autopsi di Instalasi Forensik RSUD Dr. Doris Sylvanus Tahun 2016 – 2020 - Saputra, Satria; Pangkah, Tara; Teresa, Astrid; Zaluchu, Ricka Brilianty (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2022)
Based on BPS data, the crime rate in Indonesia from 2015 – 2019 tends to decrease, But Central Kalimantan province, which is one of the provinces with the lowest population, has a high crime rate that causes death, which is 12th nationally. The aim of this research is to describe the age, gender, any type of trauma, and the location of the most common injuries on the bodies that were carried out for forensic autopsies at RSUD dr. Doris Sylvanus in 2016 – 2020. This research was a descriptive observational study with approach cross sectional (cross-sectional). From a population of 150 corpse data, 68 corpse data were obtained that met the inclusion criteria. The majority of the victims were male 53 data (81.54%). The majority of victims are adults with 66 (97.06%) bodies. Sharp trauma was the most common with 33 (48.53%) bodies followed by blunt trauma as many as 29 (42.65%) bodies. The head is the most traumatized body part, namely 27 (39.71%) bodies. Most of the sharp and blunt traumas are because the tools used are easy to get and close to everyday life. Men are involved in many murder cases because the men themselves are often involved in violence due to the influence of the hormone testosterone. Adults are mostly involved with violence because at that age they are filled with various problems such as emotional tension, increased responsibility, and so on.